High-performance sodium ferric sulfate polyanion positive electrode material and preparation method thereof

By using spray drying technology to prepare porous carbon ball particles and growing sodium ferrosulfate in situ on it, the problems of poor conductivity of sodium ferrosulfate positive electrode material and poor dispersion of carbon tubes are solved, and the preparation of high-performance sodium ferrosulfate polyanionic positive electrode material is achieved.

CN119864415AActive Publication Date: 2025-04-22TIANMU LAKE INST OF ADVANCED ENERGY STORAGE TECH CO LTD +1
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202510322467.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-22
Estimated Expiration
2045-03-19

AI Technical Summary

Technical Problem

In the prior art, the electroconductivity of sodium ferric sulfate positive electrode material is poor, the sintering temperature is low, and the in-situ carbon source coating cannot be achieved, and the dispersion effect of the carbon tube in the material is poor, resulting in a decrease in battery capacity.

Method used

Porous carbon ball particles are prepared by using linear carbon sources and spray drying technology. The mixed solution containing sodium ions, iron ions and sulfate ions is adsorbed through their porous structures to form a high-performance sodium ferrosulfate polyanionic cathode material.

Benefits of technology

A uniformly distributed conductive network and composite porous structure are achieved, which improves the electrochemical performance and stability of the material and avoids carbon source agglomeration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864415A_ABST
    Figure CN119864415A_ABST
Patent Text Reader

Abstract

The invention provides a high-performance ferric sulfate sodium polyanion positive electrode material and a preparation method thereof. The preparation method comprises the following steps: preparing a linear carbon source dispersed by a hydrophilic anion dispersant into porous carbon sphere particles with a porous structure and distributed in a three-dimensional network by adopting a spray drying technology; then adding the porous carbon sphere particles into a mixed solution containing sodium ions, iron ions and sulfate ions; adsorbing the mixed solution into the carbon spheres by using the porous structures of the porous carbon sphere particles; and drying and sintering to finally prepare the high-performance sodium ferric sulfate polyanion positive electrode material with sodium ferric sulfate growing on the porous carbon sphere particles in situ. The material is provided with a conductive layer which is uniformly distributed, and has good electrochemical performance and stability; the defects that in the prior art, a sodium ferric sulfate material is poor in conductivity, low in sintering temperature and not beneficial to in-situ sintering of a coated carbon source are effectively overcome; the application of the sodium ferric sulfate material in the battery is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and in particular relates to a high-performance sodium iron sulfate polyanion positive electrode material and a preparation method thereof. Background Art

[0002] In positive electrode materials, carbon source, as a conductive agent, has a decisive influence on the full performance of material properties. Due to the inherent poor conductivity of sodium ferric sulfate materials and the low decomposition temperature of sulfate, its sintering temperature is low, and in-situ carbon source coating cannot be achieved. At present, the preparation method of sodium ferric sulfate positive electrode materials usually adopts dry mixing of sodium salt, iron salt and carbon tubes and then sintering, but in subsequent characterization, it was found that the dispersion effect of carbon tubes in the material was not good, and there was obvious carbon tube agglomeration.

[0003] However, in the conventional dry mixing process, although attempts to disperse the nanocarbon materials can be made through long-term ball milling, a large amount of agglomeration is inevitably still present, which leads to a decrease in battery capacity.

[0004] In addition, when using the spray drying method to prepare NFS, the mixture of multiple materials leads to a high viscosity of the slurry. In order to ensure the smooth progress of the spraying process, the solid content is usually low (about 25%), while the content of carbon tubes in the aqueous solution is generally about 1%, which leads to low production efficiency, increased energy consumption, and thus increased costs. At the same time, the particle size distribution of the spray product is uneven, with a small particle size of several μm and a large particle size of more than 50 μm, which will lead to poor product consistency. The CN117720132A patent proposes the use of H 3 BO 3 , B 2 O 3 Or other boron-containing low-melting-point glass powder as a sintering aid to achieve low-temperature solid-phase sintering of the material. At the same time, water-soluble organic matter such as ascorbic acid, citric acid, glucose, etc. are used as carbon sources. Due to the low sintering temperature of sodium ferric sulfate, the organic carbon source cannot be fully carbonized, resulting in poor conductivity of the prepared material. Adding boron-containing glass powder will introduce boron impurities, affecting the purity of the material. The preparation method of modified sodium ferric sulfate positive electrode material proposed in CN118117067A first disperses the carbon source in water to obtain a carbon source dispersion; then mixes with ascorbic acid, ferrous source, sodium source, sulfur source and doped alkali metal source to obtain a suspension; then spray-drying and granulation are performed to obtain a precursor powder. This method fails to effectively disperse the carbon source. The carbon source is only added to water for ultrasonic dispersion, and the effective dispersion of the carbon source cannot be achieved.

[0005] Therefore, how to achieve effective dispersion of carbon sources and prepare sodium iron sulfate positive electrode materials with a continuous and uniform carbon conductive layer is of research significance for improving the conductivity and consistency of the material. Summary of the invention

[0006] In view of the problems in the prior art, the present invention discloses a high-performance sodium ferric sulfate polyanion cathode material and a preparation method thereof. A linear carbon source is selected and a spray drying technology is used to prepare the linear carbon source into porous carbon ball particles with a porous structure and a three-dimensional network distribution; then a mixed solution containing sodium ions, iron ions and sulfate ions is adsorbed inside the carbon ball through the porous structure; the prepared high-performance sodium ferric sulfate polyanion cathode material has a composite porous structure in which a conductive network is evenly distributed and contains a sodium ferric sulfate active material, and has good electrochemical performance and stability.

[0007] The present invention is achieved through the following technical solutions: In the first aspect, the present invention provides a high-performance sodium iron sulfate polyanion positive electrode material; the material is a porous spherical structure; the particle size of the material is 10-160nm; the pore volume is 0.010-0.040cm 3 / g; the capacity retention rate after 100 cycles of 1C charge and discharge is 96-99.8%.

[0008] As a further solution, the material satisfies (47.0-0.21*AD)*(100±8.66)%=PV*10^ 3 ; Wherein, AD represents the particle size of the high-performance sodium iron sulfate polyanion positive electrode material, and PV represents the pore volume of the high-performance sodium iron sulfate polyanion positive electrode material.

[0009] The material of the invention uses porous carbon balls composed of linear carbon as a skeleton, and sodium iron sulfate is in-situ grown on the skeleton to prepare a high-performance sodium iron sulfate polyanion positive electrode material.

[0010] In a second aspect, the present invention provides a method for preparing the high-performance sodium iron sulfate polyanion positive electrode material according to the first aspect; the preparation method comprises: S1: mixing a linear carbon source, water, and a hydrophilic anionic dispersant to obtain a carbon source slurry; S2: spray drying the carbon source slurry described in S1 to prepare porous carbon sphere particles; S3: adding the porous carbon sphere particles described in S2 to a mixed solution A containing sodium ions, iron ions, and sulfate ions to obtain a mixed solution B; allowing the sodium ions, iron ions, and sulfate ions to be adsorbed on the porous carbon sphere particles; S4: In an inert atmosphere, the mixed solution B is subjected to a heating and drying treatment, and then crushed to obtain a sodium iron sulfate polyanion precursor material; S5: Under an inert atmosphere, the sodium iron sulfate polyanion precursor material described in S4 is sintered to obtain a high-performance sodium iron sulfate polyanion positive electrode material in which sodium iron sulfate is in situ grown on porous carbon sphere particles.

[0011] As a further solution, the linear carbon source in S1 includes one or more of carbon fibers and carbon nanotubes.

[0012] As a further solution, the diameter of the linear carbon source in S1 is 5-100 nanometers; and the aspect ratio is greater than 5.

[0013] Furthermore, the diameter of the linear carbon source in S1 is preferably from 10 to 20 nanometers.

[0014] As a further solution, the type of the hydrophilic anionic dispersant in S1 is selected from one or more of a sulfate anionic dispersant and a sulfonic acid anionic dispersant; Furthermore, the sulfuric acid anion dispersant is selected from one or more of sodium lauryl sulfate and sodium polyoxyethylene fatty alcohol ether sulfate; Furthermore, the sulfonic acid anionic dispersant is selected from one or more of sodium dodecyl sulfonate and sodium styrene sulfonate.

[0015] As a further solution, the solid content of the carbon source slurry is 2-5%; the mass of the hydrophilic anionic dispersant accounts for 0.5-5% of the mass of the linear carbon source.

[0016] As a further solution, the sources of sodium ions, iron ions and sulfate ions in the S3 mixed solution A are selected from a combination of sodium sulfate sources and iron sulfate sources.

[0017] Furthermore, the sodium sulfate source is selected from one or more of sodium sulfate, anhydrous sodium sulfate, sodium thiosulfate, and sodium sulfate heptahydrate.

[0018] Furthermore, the iron sulfate source is selected from one or more of ferrous sulfate, anhydrous ferrous sulfate, ferrous sulfate monohydrate, and ferrous sulfate heptahydrate.

[0019] As a further solution, the molar concentration ratio of Na2:Fe in the S3 mixed solution A is selected from 0.5 to 1; the particle size range of the porous carbon sphere particles in S2 is 5-10 μm; the mass of the porous carbon sphere particles in S3 accounts for 2-5% of the total mass of the mixed solution B.

[0020] As a further solution, the spray drying outlet temperature in S2 is selected from 90-160 degrees; the spray drying inlet temperature is selected from 200-300 degrees.

[0021] As a further solution, in the S4 heating and drying process, the heating rate is selected from 10-20 o C / min; drying temperature is 100-130 o C; drying time is selected from 0.5-1h.

[0022] As a further solution, the particle size of the sodium iron sulfate polyanion precursor material in S4 is in the range of 5 to 20 μm.

[0023] As a further solution, the sintering temperature in S5 is 350-400 o C; the sintering treatment time is selected from 10-16h.

[0024] As a further solution, the mixing method in S1 is selected from ultrasonic dispersion; the ultrasonic dispersion power is selected from 600-2000 W; and the ultrasonic dispersion time is selected from 30-120 min.

[0025] As a further solution, the dispersion treatment in S1 is followed by a shearing treatment; the shearing power is 1500-2500 W, and the shearing treatment time is 15-60 min.

[0026] As a further solution, the mixed solution B in S3 is further subjected to ultrasonic dispersion treatment; the ultrasonic dispersion power is selected from 600-2000W; and the ultrasonic dispersion time is selected from 30-120min.

[0027] As a further solution, the inert atmosphere in S4 and S5 includes one or more combinations of nitrogen atmosphere and helium atmosphere.

[0028] In a third aspect, the present invention provides a positive electrode plate; the positive electrode plate comprises the high-performance sodium ferric sulfate polyanion positive electrode material described in the first aspect or the high-performance sodium ferric sulfate polyanion positive electrode material obtained by the preparation method described in the second aspect.

[0029] The present invention has no particular restrictions on the type of conductive agent, as long as it has the function of enhancing the conductivity of the positive electrode and does not adversely affect the performance of the high-performance sodium ferric sulfate polyanion positive electrode material. Those skilled in the art can select the conductive agent commonly used in the art according to actual needs. As some specific examples, the conductive agent used to prepare the positive electrode plate can be selected from carbon blacks such as acetylene black and conductive carbon black, conductive polymers such as carbon nanotubes, graphene, graphite, polyaniline, polythiophene, tin oxide, zinc oxide and other metal oxide conductive agents and carbon nanofiber conductive agents, etc.

[0030] The present invention does not particularly limit the type of binder, as long as it has the function of enhancing the adhesion between the positive electrode active material particles and does not adversely affect the performance of the high-performance sodium ferric sulfate polyanion positive electrode material. Those skilled in the art can make a selection according to actual needs. As some specific examples, the binder used to prepare the positive electrode plate includes polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyimide, polystyrene sulfonic acid, polyacrylonitrile, polycarbonate or polyetherimide ketone, etc.

[0031] In a fourth aspect, the present invention provides an electrode assembly, a battery cell, and an energy storage device comprising the high-performance sodium ferric sulfate polyanion positive electrode material described in the first aspect or the high-performance sodium ferric sulfate polyanion positive electrode material obtained by the preparation method described in the second aspect.

[0032] The characteristics and beneficial effects of the present invention are: (1) The present invention adopts spray drying technology to prepare a linear carbon source dispersed by a hydrophilic anion dispersant into porous carbon sphere particles with a porous structure and a three-dimensional network distribution; then the porous carbon sphere particles are added to a mixed solution containing sodium ions, iron ions and sulfate ions; the mixed solution is adsorbed inside the carbon spheres by utilizing the porous structure of the porous carbon sphere particles; after drying and sintering processes, a high-performance sodium ferric sulfate polyanion positive electrode material in which sodium ferric sulfate is in situ grown on the porous carbon sphere particles is finally obtained; the material has a uniformly distributed conductive layer; and has good electrochemical performance and stability; and provides a good reference value for the application and development of sodium ferric sulfate materials.

[0033] (2) The present invention uses a hydrophilic anionic dispersant to modify the linear carbon source, which can better inhibit the agglomeration of the linear carbon source during the preparation process; the dispersant has multiple hydrophilic groups and anionic properties, which enables it to maintain better dispersion ability in an acidic environment, and plays a good dispersing role in the preparation process of high-performance sodium ferric sulfate polyanion positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 It is the XRD diagram of the products prepared in Example 1, Example 2 and Comparative Example 1 of the present invention; wherein PDF#21-1360 is the standard curve of sodium ferric sulfate (NFS).

[0036] Figure 2 is a surface SEM image of the product prepared in Example 1 of the present invention; Figure 3 is a cross-sectional SEM image of the product prepared in Example 1 of the present invention; Figure 4 This is a surface SEM image of the product prepared in Comparative Example 1 of the present invention; Figure 5 This is a surface SEM image of the product prepared in Comparative Example 2 of the present invention; Figure 6This is a pore volume-average particle size comparison diagram of original carbon nanotubes and porous carbon sphere particles prepared in Example 1 of the present invention; Figure 7 It is a comparison chart of pore volume-average particle size of the products prepared in Example 1 of the present invention and Comparative Example 2. DETAILED DESCRIPTION

[0037] In order to facilitate the understanding of the present invention, the present invention will be described in more detail below, and embodiments of the present invention are given, but the scope of the present invention is not limited thereby.

[0038] In a first aspect, the present invention provides a method for preparing a high-performance sodium iron sulfate polyanion positive electrode material; the preparation method comprises: S1: mixing a linear carbon source, water, and a hydrophilic anionic dispersant to obtain a carbon source slurry; S2: spray drying the carbon source slurry described in S1 to prepare porous carbon sphere particles; S3: adding the porous carbon sphere particles described in S2 to a mixed solution A containing sodium ions, iron ions, and sulfate ions to obtain a mixed solution B; allowing the sodium ions, iron ions, and sulfate ions to be adsorbed on the porous carbon sphere particles; S4: In an inert atmosphere, the mixed solution B is subjected to a heating and drying treatment, and then crushed to obtain a sodium iron sulfate polyanion precursor material; S5: Under an inert atmosphere, the sodium iron sulfate polyanion precursor material described in S4 is sintered to obtain a high-performance sodium iron sulfate polyanion positive electrode material in which sodium iron sulfate is in situ grown on porous carbon sphere particles.

[0039] In view of the drawbacks of the sodium ferric sulfate material in the prior art that the conductivity is poor and the sintering temperature is low, which is not conducive to the in-situ sintering of the coated carbon source; the present invention redesigns the process path, selects a hydrophilic anion dispersant to disperse the linear carbon source, and then prepares the linear carbon source into porous carbon sphere particles with a porous structure and a three-dimensional network distribution by spray drying; then adds the linear carbon source to a mixed solution A containing sodium ions, iron ions, and sulfate ions; utilizes the porous structure of the porous carbon sphere particles to adsorb the mixed solution A inside the carbon sphere; and performs drying and sintering to prepare a high-performance sodium ferric sulfate polyanion positive electrode material in which sodium ferric sulfate is in-situ grown on the porous carbon sphere particles.

[0040] The present invention selects to use linear carbon to improve the conductivity of the sodium ferric sulfate material; this is because linear carbon has a higher specific surface area, high conductivity and good stability compared to other types of carbon sources, and is more inclined to form a stable porous structure and cross-linking and overlapping to form a three-dimensional network distribution during the preparation process; in order to subsequently fully adsorb and mix with a mixed solution A containing sodium ions, iron ions, and sulfate ions, a high-performance sodium ferric sulfate polyanion positive electrode material with a uniform conductive layer is prepared.

[0041] In addition, in order to ensure that the carbon source has good dispersibility, the present invention uses a hydrophilic anionic dispersant to modify the linear carbon source; on the one hand, the hydrophilic anionic dispersant has more hydrophilic groups, which is helpful for the dispersion of the linear carbon source. When preparing porous carbon sphere particles, the droplets produced by spray drying are quickly dried, and the linear carbon modified by the hydrophilic anionic dispersant can still remain dispersed during the drying process, avoiding the occurrence of agglomeration, and cross-linking overlaps to form a uniform three-dimensional network distribution. On the other hand, its anions help to interact with hydrogen ions in an acidic environment, generate electrostatic repulsion, and help the dispersant molecules to remain stable in the solution. The hydrophilic groups interact with water molecules, which can further improve the solubility and stability of the dispersant in the acidic solution; therefore, the modified porous carbon sphere particles are in the acidic environment of the mixed solution A containing sodium ions, iron ions, and sulfate ions; It can stably exert its dispersing effect, prevent the agglomeration between the porous carbon sphere particles, and help to adsorb the mixed solution A to form a uniform and continuous conductive layer. Furthermore, when preparing the mixed solution A, the present invention also selects to use a mixed solution A containing sodium ions, iron ions, and sulfate ions; the selection of this type of mixed solution A helps to avoid the introduction of impurity ions and ensure the purity of the prepared sodium iron sulfate polyanion positive electrode material.

[0042] The preparation method of the present invention can ensure uniform dispersion of linear carbon and promote the in-situ growth of sodium ferric sulfate on the porous carbon sphere particles to produce a high-performance sodium ferric sulfate polyanion positive electrode material by adsorbing the mixed solution A inside the porous carbon sphere particles and then drying and sintering.

[0043] As a further solution, the linear carbon source in S1 includes one or more of carbon fibers and carbon nanotubes.

[0044] As a further solution, the diameter of the linear carbon source in S1 is 5-100 nanometers; and the aspect ratio is greater than 5.

[0045] Furthermore, the diameter of the linear carbon source in S1 is preferably from 10 to 20 nanometers.

[0046] As a further solution, the type of the hydrophilic anionic dispersant in S1 is selected from one or more of a sulfate anionic dispersant and a sulfonic acid anionic dispersant; The hydrophilic anionic dispersant of the present invention contains a hydrophilic group, which can improve the dispersibility of the linear carbon source. When the spray drying technology is used to prepare porous carbon sphere particles, the improved linear carbon can maintain a dispersed state, avoid particle agglomeration, and ensure that the particles form a uniform three-dimensional network structure. The anions in the dispersant react with hydrogen ions in an acidic environment to produce electrostatic repulsion, maintaining the stability of the dispersant molecules in the solution. The hydrophilic group interacts with the water molecules to enhance the solubility and stability of the dispersant in the acidic solution. Therefore, the dispersant helps to disperse the linear carbon source, so that the porous carbon sphere particles uniformly adsorb the mixed solution A to form a uniform conductive layer, and prepare a sodium iron sulfate polyanion positive electrode material with excellent electrochemical properties.

[0047] Furthermore, the sulfuric acid anion dispersant is selected from one or more of sodium lauryl sulfate and sodium polyoxyethylene fatty alcohol ether sulfate; Furthermore, the sulfonic acid anionic dispersant is selected from one or more of sodium dodecyl sulfonate and sodium styrene sulfonate.

[0048] As a further solution, the solid content in the carbon source slurry is 2-5%; the mass of the hydrophilic anionic dispersant accounts for 0.5-5% of the mass of the linear carbon source. The appropriate solid content in the carbon source slurry helps to form uniform porous carbon sphere particles during the spray drying process, avoiding incomplete particles due to too little solid content or clogging the nozzle due to too much solid content. At the same time, the mass ratio of the hydrophilic anionic dispersant to the linear carbon source is within an appropriate range, which ensures the dispersibility and stability of the porous carbon sphere particles. It prevents the hydrophilic anionic dispersant from being too little, resulting in poor dispersion of the linear carbon source and causing agglomeration, and excessive content from affecting the slurry viscosity, resulting in discontinuous and uniform formation of porous carbon sphere particles during the spray drying process, which is not conducive to cross-linking to form a stable three-dimensional network structure. By precisely controlling these parameters, it is possible to ensure that the carbon source particles remain in a well-dispersed state during the spray drying process and avoid agglomeration, thereby preparing porous carbon sphere particles with a uniform pore structure and appropriate particle size; at the same time, it is convenient for the subsequent uniform adsorption of sodium ions, iron ions, and sulfate ions, ensuring that sodium ferric sulfate grows in situ on the porous carbon sphere particles to produce high-performance sodium ferric sulfate polyanion positive electrode materials.

[0049] As a further solution, the sources of sodium ions, iron ions and sulfate ions in the S3 mixed solution A are selected from a combination of sodium sulfate sources and iron sulfate sources.

[0050] Furthermore, the sodium sulfate source is selected from one or more of sodium sulfate, anhydrous sodium sulfate, sodium thiosulfate, and sodium sulfate heptahydrate.

[0051] Furthermore, the iron sulfate source is selected from one or more of ferrous sulfate, anhydrous ferrous sulfate, ferrous sulfate monohydrate, and ferrous sulfate heptahydrate.

[0052] As a further solution, the molar concentration ratio of Na2:Fe in the S3 mixed solution A is selected from 0.5 to 1; the particle size range of the porous carbon sphere particles in S2 is 5-10 μm; the mass of the porous carbon sphere particles in S3 accounts for 2-5% of the total mass of the mixed solution B.

[0053] The porous carbon sphere particles with a suitable particle size range obtained by spray drying help to form a uniform internal pore structure, which helps the sodium atoms, iron atoms, and sulfate ions of appropriate concentrations to be smoothly adsorbed into the internal pores of the porous carbon sphere particles; in addition, we also regulated the mass proportion of the porous carbon sphere particles in the mixed solution B; the porous carbon sphere particles with a suitable mass proportion and particle size range help the sodium iron sulfate to grow evenly attached to the porous carbon sphere particles, thereby forming a uniform conductive layer. In addition, by controlling the mass proportion of the porous carbon sphere particles, it is possible to effectively avoid the conductive layer being too thick due to too many porous carbon sphere particles, or the inability to form a continuous conductive path due to too few porous carbon sphere particles. This uniform conductive layer has an advantageous effect on improving the overall electrochemical performance of the sodium iron sulfate material.

[0054] As a further solution, the spray drying outlet temperature in S2 is selected from 90-160 degrees; the spray drying inlet temperature is selected from 200-300 degrees. By selecting the spray drying inlet and outlet temperatures in the appropriate range, it is helpful to promote the drying rate and form good and stable porous carbon sphere particles; when the inlet and outlet temperatures are set too high, it is easy to cause the structure of the dispersant and the linear carbon material to be damaged, which is not conducive to the subsequent preparation of a stable and uniform pore structure; and when the inlet and outlet temperatures are set too low, the carbon source slurry will cause agglomeration and block the spray drying outlet during the spray drying process, resulting in an unstable carbon conductive layer during the adsorption and sintering process with the mixed solution A, and the sodium iron sulfate solution is not conducive to the stable adsorption of the porous carbon sphere particles for growth, resulting in an uneven conductive layer, which cannot well improve the problem of poor conductivity of the sodium iron sulfate material.

[0055] As a further solution, in the S4 heating and drying process, the heating rate is selected from 10-20 o C / min; drying temperature is 100-130 o C; the drying time is selected from 0.5-1h. First, the porous carbon sphere particles adsorbed with the mixed solution A are dried at a suitable temperature, which helps to reduce the thermal shock caused by the rapid evaporation of water during the subsequent high-temperature sintering process. This thermal shock may cause the sodium iron sulfate solution to fail to grow smoothly along the porous carbon sphere particles, resulting in the material structure being damaged or uneven; therefore, by selecting a suitable drying temperature, it helps to ensure that the material has a relatively uniform physical state before entering the high-temperature sintering stage, forming a uniform conductive layer during the subsequent sintering process, and improving the overall performance of the material.

[0056] As a further solution, the particle size of the sodium iron sulfate polyanion precursor material in S4 is in the range of 5 to 20 μm.

[0057] As a further solution, the sintering temperature in S5 is 350-400 o C; the sintering treatment time is selected from 10-16h. Reasonable sintering temperature and time can ensure that the sodium iron sulfate material has a complete and uniform carbon conductive layer; avoid the sintering temperature being too high, which will lead to the formation of defects in the sodium iron sulfate crystal structure, destroy the adsorption stability with the carbon structure, and be unfavorable for fully combining with the carbon material, sintering to prepare a high-performance sodium iron sulfate polyanion positive electrode material, so that it has a complete and continuous coated carbon conductive layer.

[0058] As a further solution, the mixing method in S1 is selected from ultrasonic dispersion; the ultrasonic dispersion power is selected from 600-2000W; and the ultrasonic dispersion time is selected from 30-120min. S1 helps to fully mix the linear carbon source and water through ultrasonic dispersion to ensure the uniformity of the carbon source slurry. The high-frequency vibration of ultrasound can break the agglomeration between the carbon source particles, so that the carbon source particles are more evenly dispersed in the water, thereby forming more uniform porous carbon sphere particles in the subsequent spray drying process. In addition, the reasonable selection of ultrasonic dispersion power and time can further optimize the particle size distribution of the porous carbon sphere particles, making it more in line with the preparation requirements of high-performance sodium iron sulfate polyanion positive electrode materials.

[0059] As a further solution, the dispersion treatment in S1 is followed by a shearing treatment; the shearing power is 1500-2500 W, and the shearing treatment time is 15-60 min.

[0060] The shearing treatment helps to evenly disperse the linear carbon in the solution, thereby improving the uniformity and consistency of the porous carbon sphere particles after spray drying; at the same time, the shearing treatment is conducive to forming a richer pore structure after spray drying; improving the subsequent adsorption strength of the mixed solution A containing sodium ions, iron ions, and sulfate ions; and thus preparing a high-performance sodium iron sulfate polyanion positive electrode material with a uniform conductive layer.

[0061] As a further solution, the mixed solution B in S3 is further subjected to ultrasonic dispersion treatment; the ultrasonic dispersion power is selected from 600-2000W; and the ultrasonic dispersion time is selected from 30-120min. In S3, the Na ions, Fe ions, and sulfate ions in the solution are uniformly dispersed by using ultrasonic dispersion, which helps to adsorb in the pores of the porous carbon sphere particles for sintering to prepare a uniform and stable conductive layer, thereby preparing a high-performance sodium iron sulfate polyanion positive electrode material.

[0062] As a further solution, the inert atmosphere in S4 and S5 includes one or more combinations of nitrogen atmosphere and helium atmosphere.

[0063] In a second aspect, the present invention provides a high-performance sodium iron sulfate polyanion positive electrode material obtained by the preparation method described in the first aspect; the material is a porous spherical structure; the particle size of the material is 10-160nm; the pore volume is 0.010-0.040cm 3 / g; the capacity retention rate after 100 cycles of 1C charge and discharge is 96-99.8%.

[0064] As a further solution, the material satisfies (47.0-0.21*AD)*(100±8.66)%=PV*10^ 3 ; Wherein, AD represents the average particle size of the high-performance sodium iron sulfate polyanion positive electrode material, and PV represents the pore volume of the high-performance sodium iron sulfate polyanion positive electrode material.

[0065] The material of the invention uses porous carbon balls composed of linear carbon as a skeleton, and sodium iron sulfate is in-situ grown on the skeleton to prepare a high-performance sodium iron sulfate polyanion positive electrode material.

[0066] In a third aspect, the present invention provides a positive electrode plate; the positive electrode plate comprises the high-performance sodium ferric sulfate polyanion positive electrode material described in the second aspect or the high-performance sodium ferric sulfate polyanion positive electrode material obtained by the preparation method described in the first aspect.

[0067] The present invention has no particular restrictions on the type of conductive agent, as long as it has the function of enhancing the conductivity of the positive electrode and does not adversely affect the performance of the high-performance sodium ferric sulfate polyanion positive electrode material. Those skilled in the art can select the conductive agent commonly used in the art according to actual needs. As some specific examples, the conductive agent used to prepare the positive electrode plate can be selected from carbon blacks such as acetylene black and conductive carbon black, conductive polymers such as carbon nanotubes, graphene, graphite, polyaniline, polythiophene, tin oxide, zinc oxide and other metal oxide conductive agents and carbon nanofiber conductive agents, etc.

[0068] The present invention does not particularly limit the type of binder, as long as it has the function of enhancing the adhesion between the positive electrode active material particles and does not adversely affect the performance of the high-performance sodium ferric sulfate polyanion positive electrode material. Those skilled in the art can make a selection according to actual needs. As some specific examples, the binder used to prepare the positive electrode plate includes polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyimide, polystyrene sulfonic acid, polyacrylonitrile, polycarbonate or polyetherimide ketone, etc.

[0069] In a fourth aspect, the present invention provides an electrode assembly, a battery cell, and an energy storage device comprising the high-performance sodium ferric sulfate polyanion positive electrode material described in the second aspect or the high-performance sodium ferric sulfate polyanion positive electrode material obtained by the preparation method described in the first aspect.

[0070] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0071] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.

[0072] Example 1 S1: 4 g of carbon nanotubes with a diameter of 15±2 nm and an aspect ratio of 7±2 nm, 79.8 g of water, and 0.2 g of sodium dodecyl sulfate are added into a container; ultrasonic dispersion is performed, the ultrasonic dispersion power is set to 800 W, and the ultrasonic dispersion time is set to 60 min; then shearing is performed using an emulsifier with a shear power of 2000 W and a shear time of 15 min; stirring is performed to obtain a carbon source slurry; wherein the solid content in the carbon source slurry is adjusted to 5%, and the mass ratio of sodium dodecyl sulfate to carbon nanotubes is 5%.

[0073] S2: The carbon source slurry obtained in S1 is spray dried, and the fan is 90 CFM to prepare porous carbon sphere particles. The outlet temperature of the spray drying is set to 120 degrees, and the inlet temperature is set to 250 degrees. The particle size range of the obtained porous carbon sphere particles is controlled to be 7 μm.

[0074] S3: 17 g of anhydrous sodium sulfate and 30 g of ferrous sulfate were added to 50 g of water, and stirred at 500 rpm / min for 60 min at 50 degrees to obtain a mixed solution A. The molar concentration ratio of Na2:Fe in the mixed solution A was 0.6. The pH value of the mixed solution A was about 4.

[0075] S3: 2 grams of the porous carbon sphere particles obtained in S2 were added to the mixed solution A in S3, and ultrasonic stirring was performed at a power of 2000 W for 120 minutes for dispersion treatment to obtain a mixed solution B. The mass of the porous carbon sphere particles accounted for 2% of the total mass of the mixed solution B.

[0076] S4: Under nitrogen atmosphere, tube furnace temperature curve 15 o C / min heating up to 120 o C, keep for 1 hour, and heat the mixed solution B to dry it. Then, mechanically crush it; the crushed particle size is 5 μm; and the sodium iron sulfate polyanion precursor material is obtained.

[0077] S5: Continuing in a nitrogen atmosphere, the sodium iron sulfate polyanion precursor material obtained in S4 was placed into a sagger, the temperature was raised to 370°C at 10°C / min, and pressure sintered for 12 hours to finally obtain a high-performance sodium iron sulfate polyanion positive electrode material.

[0078] Energy consumption calculation: In order to obtain 1 ton of sodium iron sulfate-CNT composite material, 40 kg of carbon nanotubes, 10 kg of dispersant, and 760 kg of water are needed for spray drying. 760 kg of water needs to be evaporated to obtain 40 kg of porous carbon sphere particles. After mixing 40 kg of CNT spheres with 1920 kg of an aqueous solution containing 50% NFS salt and drying, only 800*95%+1920*50%=1.72 tons of water need to be evaporated.

[0079] Example 2 The specific steps and preparation method are the same as those in Example 1, except that sodium dodecyl sulfate dispersant is used.

[0080] Example 3 The specific steps and preparation method are the same as those in Example 1, except that the solid content in the carbon source slurry is adjusted to 4%, and the mass ratio of sodium dodecyl sulfate to carbon nanotubes is 1%.

[0081] Example 4 The specific steps and preparation method are the same as those in Example 1, except that the mass of the porous carbon sphere particles accounts for 3% of the total mass of the mixed solution B.

[0082] Example 5 The specific steps and preparation method are the same as those in Example 1, except that the mass of the porous carbon sphere particles accounts for 5% of the total mass of the mixed solution B.

[0083] Example 6 The specific steps and preparation method are the same as those in Example 1, except that in S1, the ultrasonic dispersion power is set to 600 W, and the ultrasonic dispersion time is set to 40 min.

[0084] Example 7 The specific steps and preparation method are the same as those in Example 1, except that the outlet temperature of the spray drying is set to 90 degrees and the inlet temperature is set to 200 degrees. The particle size range of the obtained porous carbon sphere particles is controlled to be 10 μm.

[0085] Example 8 The specific steps and preparation method are the same as those in Example 1, except that: in S4, under a nitrogen atmosphere, the temperature curve of the tube furnace is 10 o C / min heating up to 100 o C, hold for 1 hour, and dry the mixed solution B at a high temperature.

[0086] Example 9 The specific steps and preparation method are the same as those in Example 1, except that: in S5: continue to put the sodium iron sulfate polyanion precursor material obtained in S4 into a sagger under a nitrogen atmosphere, raise the temperature to 400°C at 15°C / min, and sinter under pressure for 10 hours to finally obtain a high-performance sodium iron sulfate polyanion positive electrode material.

[0087] Comparative Example 1 The specific steps and preparation method are the same as those in Example 1, except that polyvinyl pyrrolidone dispersant is used.

[0088] Comparative Example 2 S1: 4 g of carbon nanotubes with a diameter of 15±2 nm and an aspect ratio of 6±2 nm, 79.8 g of water, 0.2 g of sodium dodecyl sulfate, 17 g of anhydrous sodium sulfate and 30 g of ferrous sulfate are added into a container; ultrasonic dispersion is performed, the ultrasonic dispersion power is set to 800 W, and the ultrasonic dispersion time is set to 60 min; a mixed slurry is obtained; S2: Spray dry the mixed slurry obtained in S1, and prepare porous carbon sphere particles with a fan of 90 CFM. The outlet temperature of the spray dryer is set to 120 degrees, and the inlet temperature is set to 250 degrees. Particles with a particle size of 5 μm are obtained; S3: Directly heat the pellets in S2 to a temperature curve of 15 o C / min to 370°C and sintered under pressure for 12 hours to obtain the sodium iron sulfate polyanion positive electrode material.

[0089] Energy consumption calculation: In order to obtain 1 ton of sodium iron sulfate-CNT composite material, a slurry of 1% CNT, 24% NFS salt, and 75% water is spray-dried. 40 kg of carbon nanotubes, 10 kg of dispersant, 1920 kg of NFS salt, and 3 tons of water are needed to mix, and 3 tons of water needs to be evaporated for spray drying.

[0090] Comparative Example 3 The specific steps and preparation method are the same as those in Example 1, except that: in S3, the mass of the porous carbon sphere particles accounts for 10% of the total mass of the mixed solution B.

[0091] Comparative Example 4 The specific steps and preparation method are the same as those in Example 1, except that: in S3, the mass of the porous carbon sphere particles accounts for 1% of the total mass of the mixed solution B.

[0092] Comparative Example 5 The specific steps and preparation method are the same as those in Example 1, except that the outlet temperature of the spray drying is set to 60 degrees and the inlet temperature is set to 100 degrees. The particle size of the obtained porous carbon sphere particles is in the range of 20±5 μm.

[0093] Comparative Example 6 The specific steps and preparation methods of S1-S3 are the same as those of Example 1, except that: the mixed solution B is directly heated to a temperature curve of 15 o C / min to 370°C and sintered under pressure for 12 hours to obtain the sodium iron sulfate polyanion positive electrode material.

[0094] Specific test methods and conditions Sodium iron sulfate, carbon black, and PVDF were mixed evenly in a mass ratio of 90:5:5, and coated on aluminum foil using a 100um four-sided preparation device. The electrode film was then pre-dried in an 80°C blast drying oven for 30 minutes and then transferred to a vacuum drying oven at 110°C for 10 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a punching machine. Metal sodium was used as the counter electrode, and 1M NaClO 4 EC+DEC (1:1 vol%)+5%FEC was used as the electrolyte and Whatman-D glass fiber separator was used to assemble CR2032 button cells in a glove box.

[0095] The button cell was subjected to constant current charge and discharge tests with a current density of 0.1C (1C=100mAh / g). Within the voltage range of 2.0-4.3V, 0.1C / 0.5C / 2C / 5C discharge specific capacity tests were performed, as well as 100 cycles at a rate of 1C.

[0096] Table 1

[0097] It can be seen from the data in Table 1 that the embodiments have better electrochemical performance than the comparative examples; the discharge specific capacities of embodiments 1 to 9 are all higher than those of comparative examples 1 to 6, and the rate performance and cycle performance are more stable. This shows that the preparation method of the present invention has obvious advantages in improving the electrochemical properties such as conductivity and cycle stability of the sodium iron sulfate positive electrode material.

[0098] Specifically, it can be seen from the embodiment and comparative example 1 that, relative to the present embodiment, when comparative example 1 uses a polyvinyl pyrrolidone non-hydrophilic anionic dispersant, the discharge specific capacity, cycle efficiency and other properties of the positive electrode material prepared are relatively poor; this is because the dispersant used in the present invention not only has good dispersibility and high conductivity, but also has good stability in an acidic solution containing sulfate ions, which can effectively avoid the deactivation of the dispersant, and in the process of sintering to prepare a high-performance sodium ferric sulfate polyanion positive electrode material, it can effectively ensure the dispersibility of the carbon source and prevent agglomeration to form an uneven and continuous conductive layer. The dispersant used in the embodiment helps to prepare a uniform and continuously coated carbon conductive layer, so that it not only has a high conductivity and charge and discharge specific capacity, but also maintains the stability of the sodium ferric sulfate structure, and has a better cycle efficiency.

[0099] It can be seen from the embodiment and comparative example 2 that the difference between comparative example 2 and the present embodiment is that in the process of preparing high-performance sodium ferric sulfate positive electrode material by carbon coating, comparative example 2 selects the carbon source, dispersant, ferrous sulfate, and anhydrous sodium sulfate to be directly mixed for spray drying, and then sintering preparation operation steps are performed; this preparation method easily leads to the formation of uneven carbon source coating, and the carbon source is prone to agglomeration. At the same time, this preparation method also increases the process difficulty of spray drying preparation, resulting in blockage, and easily causing structural collapse during high-temperature sintering; it is not conducive to the formation of a high-performance sodium ferric sulfate polyanion positive electrode material with a stable structure and a uniform and continuous carbon layer.

[0100] It can be seen from the embodiment and comparative examples 3 and 4 that in the process of preparing high-performance sodium ferric sulfate positive electrode materials by drying and sintering, the electrochemical performance and cycle stability of the embodiment are better than those of comparative examples 3 and 4. This is because the embodiment selects a suitable range of the proportion of porous carbon sphere particles and mixed solution B, which can ensure that the sodium ferric sulfate solution in the mixed solution B can grow evenly on the surface of the porous carbon sphere particles, thereby forming a uniform conductive layer. However, in comparative examples 3 and 4, if the proportion of porous carbon sphere particles is too high or too low, it is easy to cause the conductive layer to be too thick or unable to form a continuous conductive path, which is not conducive to improving the problem of poor conductivity of the sodium ferric sulfate material.

[0101] It can be seen from Comparative Example 5 and the embodiment that Comparative Example 5 selects different spray drying conditions, and the inlet and outlet temperatures are lower than those of the present embodiment, and the electrochemical performance of the prepared high-performance sodium iron sulfate polyanion material is lower during the battery charge and discharge cycle; this is because when the spray drying temperature is too low, it is easy to cause the carbon source slurry to agglomerate during the spray drying process, blocking the spray drying outlet, and the prepared porous carbon sphere particles are uneven in particle size, which is not conducive to having a porous structure and a three-dimensional network structure with cross-linked overlaps. At the same time, excessive moisture affects its drying and sintering rate, which is not conducive to reducing the growth bonding force between sodium iron sulfate and the carbon structure during the sintering preparation process, while Example 1 selects a suitable range of spray drying inlet and outlet temperatures, which helps the carbon source slurry to prepare carbon source particles with good porous structure and uniform particle size. Thus, a sodium iron sulfate polyanion positive electrode material with high performance is successfully prepared.

[0102] In Comparative Example 6, steps S4 and S5 are combined relative to the embodiment; the positive electrode material prepared by this method exhibits poor electrochemical performance and cycle stability during the battery cycle compared to the embodiment; this is because when the porous carbon ball particles adsorbed by mixed solution A are directly sintered, the presence of water will cause thermal shock during the sintering process, resulting in the inability of sodium iron sulfate to grow smoothly along the porous carbon ball particles; resulting in unstable bonding with the carbon conductive layer, easily causing structural defects; thereby affecting the structural stability during the cycle, and at the same time, structural defects will also cause uneven bonding with the carbon conductive layer, which is not conducive to improving the electrochemical performance.

[0103] pass Figure 1 It can be seen from the XRD performance diagrams of Comparative Example 1, Example 1 and Example 2 that the peaks of Examples 1 and 2 are consistent with those of the standard card of NFS, and the purity of the obtained material is higher than that of Comparative Example 1. Comparative Example 1 has obvious impurity peaks that will affect the performance of the material.

[0104] pass Figure 2 , Figure 3 From the SEM image of Example 1, it can be seen that Figure 2 , 3 are the surface and cross-sectional SEM images of the carbon spheres after spraying, respectively. Figure 3 It can be seen that the porous carbon sphere particles after spraying have evenly distributed pores, which helps the NFS salt solution to be better and more evenly filled and tightly combined with the carbon tubes. Figure 2 , so that it can obtain better conductive properties.

[0105] pass Figure 4 From the SEM image of the NFS surface after spraying in Comparative Example 1, it can be seen that NFS accumulates on the surface of the sphere, and there is a clear boundary between the carbon tubes and NFS, which cannot achieve good conductivity.

[0106] pass Figure 5From the SEM image of Comparative Example 2, it can be seen that the carbon tubes have obvious agglomeration inside the particles, and NFS and the carbon tubes are not well combined, thus affecting the performance of the material.

[0107] pass Figure 6 as well as Figure 7 It can be seen that the product prepared in Example 1 can have a deeper pore volume at the same particle size compared with Comparative Example 2, and can be better combined with the sodium iron sulfate material. In addition, the average particle size and pore volume of the product prepared in Example 1 of the present invention also satisfy the formula (47.0-0.21*AD)*(100±8.66)%=PV*10^ 3 .

[0108] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-performance sodium iron sulfate polyanion positive electrode material; characterized in that: The material has a porous spherical structure; the particle size of the material is 10-160nm; the pore volume is 0.010-0.040cm 3 / g; the capacity retention rate after 100 cycles of 1C charge and discharge is 96-99.8%.

2. The high-performance sodium iron sulfate polyanion positive electrode material according to claim 1; characterized in that: The material satisfies (47.0-0.21*AD)*(100±8.66)%=PV*10^ 3 ; Wherein, AD represents the particle size of the high-performance sodium iron sulfate polyanion positive electrode material, and PV represents the pore volume of the high-performance sodium iron sulfate polyanion positive electrode material.

3. A method for preparing the high-performance sodium iron sulfate polyanion positive electrode material according to any one of claims 1-2; characterized in that: The preparation method comprises: S1: mixing a linear carbon source, water, and a hydrophilic anionic dispersant to obtain a carbon source slurry; S2: spray drying the carbon source slurry described in S1 to prepare porous carbon sphere particles; S3: adding the porous carbon sphere particles described in S2 to a mixed solution A containing sodium ions, iron ions, and sulfate ions to obtain a mixed solution B; allowing the sodium ions, iron ions, and sulfate ions to be adsorbed on the porous carbon sphere particles; S4: In an inert atmosphere, the mixed solution B is subjected to a heating and drying treatment, and then crushed to obtain a sodium iron sulfate polyanion precursor material; S5: Under an inert atmosphere, the sodium iron sulfate polyanion precursor material described in S4 is sintered to obtain a high-performance sodium iron sulfate polyanion positive electrode material in which sodium iron sulfate is in situ grown on porous carbon sphere particles.

4. The method for preparing the high-performance sodium iron sulfate polyanion positive electrode material according to claim 3; characterized in that: The linear carbon source in S1 includes one or more of carbon fiber and carbon nanotube; the solid content in the carbon source slurry is 2-5%; the mass of the hydrophilic anionic dispersant accounts for 0.5-5% of the mass of the linear carbon source; Furthermore, the diameter of the linear carbon source in S1 is 5-100 nanometers; the aspect ratio is greater than 5; Furthermore, the diameter of the linear carbon source in S1 is preferably from 10 to 20 nanometers.

5. The method for preparing the high-performance sodium iron sulfate polyanion positive electrode material according to claim 3; characterized in that: The sources of sodium ions, iron ions and sulfate ions in the S3 mixed solution A are selected from a combination of sodium sulfate sources and iron sulfate sources; Further, the sodium sulfate source is selected from one or more of sodium sulfate, anhydrous sodium sulfate, sodium thiosulfate, and sodium sulfate heptahydrate; Furthermore, the iron sulfate source is selected from one or more of ferrous sulfate, anhydrous ferrous sulfate, ferrous sulfate monohydrate, and ferrous sulfate heptahydrate.

6. The method for preparing the high-performance sodium iron sulfate polyanion positive electrode material according to claim 3; characterized in that: The molar concentration ratio of Na2:Fe in the S3 mixed solution A is selected from 0.5 to 1; the particle size range of the porous carbon sphere particles in the S2 is 5-10 μm; the mass of the porous carbon sphere particles in the S3 accounts for 2-5% of the total mass of the mixed solution B.

7. The method for preparing the high-performance sodium iron sulfate polyanion positive electrode material according to claim 3; characterized in that: The spray drying outlet temperature in S2 is selected from 90-160 degrees; the spray drying inlet temperature is selected from 200-300 degrees; the particle size range of the sodium iron sulfate polyanion precursor material in S4 is 5-20 μm.

8. The method for preparing the high-performance sodium iron sulfate polyanion positive electrode material according to claim 3; characterized in that: In the S4 heating and drying process, the heating rate is selected from 10-20 o C / min; drying temperature is 100-130 o C; drying time is selected from 0.5-1h; Furthermore, the sintering temperature in S5 is between 350 and 400 o C; sintering time is selected from 10-16h; Furthermore, the inert atmosphere in S4 and S5 includes one or more combinations of nitrogen atmosphere and helium atmosphere.

9. A positive electrode sheet; characterized in that: The positive electrode plate comprises the high-performance sodium ferric sulfate polyanion positive electrode material according to any one of claims 1-2 or the high-performance sodium ferric sulfate polyanion positive electrode material obtained by the preparation method according to any one of claims 3-8.

10. An electrode assembly, a battery cell or an energy storage device; characterized in that: The high-performance sodium ferric sulfate polyanion positive electrode material comprises the high-performance sodium ferric sulfate polyanion positive electrode material described in any one of claims 1-2 or the high-performance sodium ferric sulfate polyanion positive electrode material obtained by the preparation method described in any one of claims 3-8.

Citation Information

Patent Citations

  • Sodium ferric sulfate as well as preparation method and application thereof

    CN117720132A

  • Modified sodium ferric sulfate positive electrode material and preparation method thereof, and secondary battery

    CN118117067A

  • Carbon composite iron-based polyanion positive electrode material and preparation method thereof

    CN115188951A

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN116239154A

  • Sodium ion battery

    CN116404144A